2017
DOI: 10.1680/jgeot.15.p.200
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of first-time slope failures using acoustic emission measurements: large-scale physical modelling

Abstract: Early warning systems for slope instability need to alert users of accelerating slope deformation behaviour to enable safety-critical decisions to be made. This study shows that acoustic emission (AE) monitoring of active waveguides (i.e. a steel tube with a granular backfill surround installed through a slope) can both detect shear surface development and quantify increasing rates of movement during slope failure, thereby providing an early detection of slope instability. A large-scale physical model was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 24 publications
3
71
0
Order By: Relevance
“…Extensive research including multiple field trials (e.g. Berg et al 2018;Dixon et al 2015a;Dixon et al 2015b;Smith and Dixon 2015;Smith et al 2014;Smith et al 2017a) has demonstrated that AE rates are indicative of slope displacement rates, and hence, this instrumentation is defined as a slope displacement rate sensor. Activity status of the slope (e.g.…”
Section: Slope Alarmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive research including multiple field trials (e.g. Berg et al 2018;Dixon et al 2015a;Dixon et al 2015b;Smith and Dixon 2015;Smith et al 2014;Smith et al 2017a) has demonstrated that AE rates are indicative of slope displacement rates, and hence, this instrumentation is defined as a slope displacement rate sensor. Activity status of the slope (e.g.…”
Section: Slope Alarmsmentioning
confidence: 99%
“…Accelerating landslide events have been simulated in two ways: (i) a large scale simulated first-time landslide failure experiment using a waveguide with external fill to compare performance of CSS directly with the published performance of the Slope ALARMS system (Smith et al 2017a) and (ii) series of experiments conducted using displacement-controlled bending tests on active waveguides with internal fill to understand repeatability and establish relationships between AE and displacement rates for different tube diameters and infill types. In all tests, the waveguides were subjected to accelerating deformations to replicate known behaviour in first-time landslides, which accelerate as Fig.…”
Section: Css Performance Evaluation Using Physical Model Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generated AE rates are proportional to applied displacement rates, where the coefficient of proportionality Smith et al Monitoring Buried Pipe Deformation Using AE: Quantification of Attenuation 17/08/2016 3 is dependent on the depth to the shear surface and the distance AE propagates along the waveguide to the ground surface where it is measured. Quantifying this magnitude of attenuation for each installation is essential to deriving slope displacement rates from measured AE rates, which can be used to warn users of accelerating slope deformation behaviour to enable evacuation of vulnerable people and timely repair and maintenance of critical infrastructure (Koerner et al, 1981;Nakajima et al, 1991;Smith et al, 2014a;Smith et al, 2014b;Dixon et al, 2015a;Dixon et al, 2015b;Smith, 2015;Smith & Dixon, 2015;Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%